2020
DOI: 10.1371/journal.pone.0234660
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two methods to predict the incidence of hepatitis B in Guangxi, China

Abstract: In recent years, the incidence of hepatitis B (HB) in Guangxi is higher than that of the national level; it has been increasing, so it is urgent to do a good predictive research of HB incidence, which can help analyze the early warning of hepatitis B in Guangxi, China. In the study, the feasibility of predicting HB incidence in Guangxi by autoregressive integrated moving average (ARIMA) model method and Elman neural network (ElmanNN) method was discussed respectively, and the prediction accuracy of the two mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In other fields, such as economics and transportation, the ARIMA-ERNN model has been found to provide better predictive accuracy than other models [ 30 , 31 ]. However, epidemiologists have only rarely used the ARIMA-ERNN model for the prediction of infectious diseases [ 32 ]. To the best of our knowledge, the present study constitutes the first use of a combined ARIMA-ERNN model to predict the incidence of pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…In other fields, such as economics and transportation, the ARIMA-ERNN model has been found to provide better predictive accuracy than other models [ 30 , 31 ]. However, epidemiologists have only rarely used the ARIMA-ERNN model for the prediction of infectious diseases [ 32 ]. To the best of our knowledge, the present study constitutes the first use of a combined ARIMA-ERNN model to predict the incidence of pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that according to the data features of the study, choosing the right model is a prerequisite for exploring credible results. Based on a literature review and our previous research, we found that the ARIMA, [3] GM (1, 1) model, [3] Decision tree, [32] Random forest, [32] AdaBoost with decision tree (AdaBoost), [32] extreme gradient boosting decision tree (XGBoost), [32] Elman network, [33] and generalized regression neural network (GRNN) [34] can be used to predict hepatitis B. Among these, the GM (1,1) model is suitable for short-term prediction with small sample sizes [17] .…”
Section: Discussionmentioning
confidence: 99%
“…We then apply the combined forecasting model for prediction, such as the SARIMA-NARNNX hybrid model, [45] SARIMA-NAR hybrid model, [46] and SARIMA-SDGM hybrid prediction model [47] . Third, almost all prediction techniques have defects; therefore, the prediction results only take references [33] . We should adopt a correct attitude towards the prediction results and use them to guide practical work, rather than regarding the prediction results as an exclusive policy-making reference frame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of forecasting the incidence of hepatitis B, Wang et al found that ARIMA model showed better forecasting performance than GM(1,1) model [ 16 ]. Zheng et al showed that ELMAN model was superior to ARIMA (0,1,1) model in predicting the incidence of hepatitis B in Guangxi through comparative experiments [ 17 ]. In addition, Wei et al announced that the ARIMA-GRNN mixed model performs better than the ARIMA model and the GRNN model in predicting the incidence of hepatitis [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%